Interaction of the erythroid transcription factor cGATA-1 with a critical auto-regulatory element. - Schwartzbauer, G (1992)
We have performed a mutational analysis of the promoter for the chicken erythroid-specific GATA-1 transcription factor, and have investigated in detail the interaction of the factor with an upstream auto-regulatory element (ARE). We find that a single proximal GATA binding site of the ARE is required for promoter activity in primary erythroid cells; however, this minimal promoter is inappropriately active in fibroblasts. At least two molecules of GATA-1 can interact with the ARE, and sequences outside of the consensus site appear critical for the transcriptional activity of the bound protein. Finally, we provide evidence for complex protein/DNA interactions at the ARE, including the ability of GATA-1 to bend DNA.